2019
DOI: 10.1039/c9ta02886b
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient alkaline HER Co–Mo bimetallic carbide catalyst with an optimized Mo d-orbital electronic state

Abstract: A Co–Mo bimetallic carbide catalyst with an optimized electronic state was fabricated and great alkaline HER performance was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Similarly, Liu et al experimentally explored the effect of introducing metallic Co into β-Mo 2 C materials on the HER performance. Their results show that Co-doped β-Mo2C could promote the HER activity . Li et al.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, Liu et al experimentally explored the effect of introducing metallic Co into β-Mo 2 C materials on the HER performance. Their results show that Co-doped β-Mo2C could promote the HER activity . Li et al.…”
Section: Introductionmentioning
confidence: 95%
“…One strategy to improve the catalytic activity of catalysts is to utilize the defect and interface engineering (e.g., vacancy, doping, and loading). ,, Recently, single-atom alloys catalysts based on MXenes substrates have been extensively studied as alternative catalysts for various catalytic reactions. ,, For example, Zhang et al synthesized the Mo 2 TiC 2 T x –Pt SA catalyst with the single-atom Pt dispersed on the Mo vacancy of Mo 2 TiC 2 T x nanosheets, and these alloy-catalysts exhibit high activity toward HER . Similarly, Liu et al experimentally explored the effect of introducing metallic Co into β-Mo 2 C materials on the HER performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the active β ‐phase Mo 2 C has been initially discovered in 2012, the research of Mo 2 C was increased rapidly although it‘s activity was not yet preeminent enough to unseat Pt‐based catalyst [12] . Further studies indicated that the excessively powerful Mo−H binding energy hindered the desorption of H ads to form hydrogen, which was the main factor effecting the catalytic performance of Mo 2 C. By doping the electron‐rich transition metals (such as Fe, Co, Ni and other elements in VIII group) to decrease the occupied d orbital of Mo, or building abundant defects on the surface can transform the surface charge density distribution of the catalyst, so as to optimize the intensity of the Mo−H bond, and then promote the electrocatalytic activity of Mo 2 C [13–19] . For example, Gao et al.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Since the active β-phase Mo 2 C has been initially discovered in 2012, the research of Mo 2 C was increased rapidly although it's activity was not yet preeminent enough to unseat Pt-based catalyst. [12] Further studies indicated that the excessively powerful MoÀ H binding energy hindered the desorption of H ads to form hydrogen, which was the main factor effecting the catalytic performance of Mo 2 C. By doping the electron-rich transition metals (such as Fe, Co, Ni and other elements in VIII group) to decrease the occupied d orbital of Mo, or building abundant defects on the surface can transform the surface charge density distribution of the catalyst, so as to optimize the intensity of the MoÀ H bond, and then promote the electrocatalytic activity of Mo 2 C. [13][14][15][16][17][18][19] For example, Gao et al successfully doped Co in Mo 2 C nanowires, which significantly increased the electron density around the Fermi level in Mo 2 C and weakened the adverse effect of MoÀ H on HER kinetics, rendering the prepared Co-Mo 2 C was able to reach 10 mA cm À 2 at 140 mV. [20] Li and her co-worker employed SiO 2 as a hard template to synthesize β-Mo 2 C nanoparticles with rich Mo vacancies by dangerous hydrofluoric acid (HF) etching, which showed excellent HER activity.…”
Section: Introductionmentioning
confidence: 99%